Superior bioavailability of EPA and DHA from a L-lysine salt formulation: a randomized, three-way crossover study - Christiane Schön; Antje Micka; Vishnupriya Gourineni; Roberta Bosi (Food & Nutrition Research)
Background: Omega-3 fatty acids, including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are polyunsaturated fatty acids (PUFAs) with notable health benefits. Due to limited physiological production and insufficient dietary supply, external supplementation is important. Objective: This study aimed to compare the pharmacokinetics and bioavailability of EPA and DHA in AvailOm® omega-3-lysine salt (Lys-FFA) versus standard ethyl ester (EE) and triglyceride (TG) formulations after a single oral dose in healthy subjects. Design: A randomized, three-way crossover study was conducted with 21 healthy subjects. Results: Twenty-one subjects (10 men, 11 women) completed the study. The average age was 41.7 years, and the mean body mass index was 23.0 kg/m2. The Lys-FFA formulation showed significantly higher uptake of omega-3 fatty acids (EPA+DHA combined and each individually) compared to EE. Specifically, Lys-FFA had a 9.33-fold (0–12 h) and 8.09-fold (0–24 h) higher bioavailability of EPA+DHA than EE and a 1.57-fold (0–12 h) and 1.44-fold (0–24 h) higher bioavailability than TG. ΔCmax and Tmax also favored Lys-FFA over EE. Discussion: Under fasting conditions, the absorption of EPA and DHA from EE is limited due to the need for enzymatic cleavage before absorption. This requirement is bypassed with Lys-FFA, which does not need cleavage. Conclusions: The study demonstrates that EPA and DHA lysine salt (Lys-FFA) offers superior bioavailability compared to EE and triglyceride forms, presenting a more effective supplementation option.German Clinical Trials Register, DRKS-ID: DRKS00029183